Humidity Sensing of Stretchable and Transparent Hydrogel Films for Wireless Respiration Monitoring - Liang, Yuning; Ding, Qiongling; Wang, Hao; Wu, Zixuan; Li, Jianye; Li, Zhenyi; Tao, Kai; Gui, Xuchun; Wu, Jin (Nano-Micro Letters, 2022)
Respiratory monitoring plays a pivotal role in health assessment and provides an important application prospect for flexible humidity sensors. However, traditional humidity sensors suffer from a trade-off between deformability, sensitivity, and transparency, and thus the development of high-performance, stretchable, and low-cost humidity sensors is urgently needed as wearable electronics. Here, ultrasensitive, highly deformable, and transparent humidity sensors are fabricated based on cost-effective polyacrylamide-based double network hydrogels. Concomitantly, a general method for preparing hydrogel films with controllable thickness is proposed to boost the sensitivity of hydrogel-based sensors due to the extensively increased specific surface area, which can be applied to different polymer networks and facilitate the development of flexible integrated electronics. In addition, sustainable tapioca rich in hydrophilic polar groups is introduced for the first time as a second cross-linked network, exhibiting excellent water adsorption capacity. Through the synergistic optimization of structure and composition, the obtained hydrogel film exhibits an ultrahigh sensitivity of 13,462.1%/%RH, which is unprecedented. Moreover, the hydrogel film-based sensor exhibits excellent repeatability and the ability to work normally under stretching with even enhanced sensitivity. As a proof of concept, we integrate the stretchable sensor with a specially designed wireless circuit and mask to fabricate a wireless respiratory interruption detection system with Bluetooth transmission, enabling real-time monitoring of human health status. This work provides a general strategy to construct high-performance, stretchable, and miniaturized hydrogel-based sensors as next-generation wearable devices for real-time monitoring of various physiological signals. Highlights: 1 A general strategy of fabricating thickness-controllable hydrogel films with diverse polymer networks for humidity sensing is proposed. The hydrogel film humidity sensor displays an unprecedented sensitivity up to 13,462.1%/%RH. 2 The stretchable humidity sensor can work normally under large tensile strains with even enhanced sensitivity, which makes the humidity responding property of hydrogel mechanically programmable. 3 A wireless respiratory interruption detection mask with Bluetooth transmission function is developed based on the sensor, enabling the real-time, wireless and accurate acquisition of user’s breathing state, such as the interval and breathing frequency and apnea.